The Contribution of Psychoanalysis to Organization Studies and Management: An Overview - Arnaud, Gilles (Organization studies, 2012)
A prolific current of research focusing on the psychodynamics of work, leadership and organizations has taken form over approximately the last 60 years. The richness of this current remains in full evidence today and shows the interest of applying psychoanalysis to research work on management. First, psychoanalysis can aid researchers to develop a more profound comprehension of organizational functioning by taking into account the effects of the unconscious. Second, it can guide them in different fields of intervention by transposing aspects of the analytical treatment and integrating transference. Last, it can allow them to re-question managerial ends from a slightly ‘askew’ point of view informed by psychoanalytic ethics and recognition of the ‘subject’. This review article aims at examining these issues and offering psychoanalytic theory as a paradigm for the study of management.